Hubungan Kecemasan Dengan Kualitas Hidup Pasien Dalam Pengobatan OAT Di Poliklinik DOTS: ANXIETY ABOUT PATIENTS' QUALITY OF LIFE IN OAT TREATMENT AT THE DOTS POLYCLINIC - Siagian, Ira Ocktavia (Jurnal Keperawatan Muhammadiyah, 2024)
Tuberculosis (TB) is an infectious disease which is mostly caused by Mycobacterium tuberculosis bacteria which enter the human body through respiratory air into the lungs and can spread from the lungs to other parts of the body. Improving quality of life is important as a goal of successful treatment and is the key to healing pulmonary TB sufferers. The aim of this study was to determine the relationship between anxiety levels and the quality of life of patients undergoing OAT treatment at the DOTS polyclinic at Immanuel Hospital Bandung. This research design uses an analytical survey research design with a cross sectional approach. The population in the study were all outpatient tuberculosis patients at the DOTS polyclinic at Immanuel Hospital. The sampling technique in this research was probability sampling of 75 respondents. The instrument of this research is a questionnaire. Data analysis uses univariate and bivariate. There is a significant relationship between the level of anxiety and the quality of life of patients in OAT treatment at the DOTS Polyclinic, Immanuel Hospital Bandung. The level of anxiety level of patients in OAT treatment at the DOTS Polyclinic, Immanuel Hospital Bandung, the majority of respondents (70.6%) had mild anxiety, the quality of life of patients undergoing OAT treatment at the DOTS Polyclinic, Immanuel Hospital Bandung, the majority of respondents (64%), high quality of life, There is a significant relationship between the level of anxiety and the quality of life of patients in OAT treatment at the DOTS Polyclinic, Immanuel Hospital Bandung. It is hoped that the results of this research can be used as a reference for an intervention to reduce anxiety levels by coordinating with the patient and the patient's family in explaining the importance of providing education related to anxiety and quality of life for patients undergoing OAT treatment at the DOTS Polyclinic, Immanuel Hospital, Bandung.